1978
DOI: 10.1094/phyto-68-517
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Yield Losses in Corn from Southern Corn Leaf Blight

Abstract: The effect of southern corn leaf blight caused by disease severities assessed at the dough stage in each year. Helminthosporium maydis race T on corn in Texas male-Regression coefficients were 0.69 in 1975 and 0.70 in 1976 (R 2 sterile cytoplasm was investigated in the field in 1975 and = 86.3 and 87.0%, respectively). Values for y-intercepts for 1976. Losses in yield of grain due to infection initiated late in these equations were not significantly different from zero (P the season were 9.7 to 11.7%. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Single point models have been used for several diseases including, corn leaf southern blight (Bipolaris maydis) (Gregory et al 1978), potato late blight (Phytophthora infestans) (Olofson 1968). Integral model was used for wheat stem rust (Puccinia graminis) crop loss assessment for the first time (Teng 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Single point models have been used for several diseases including, corn leaf southern blight (Bipolaris maydis) (Gregory et al 1978), potato late blight (Phytophthora infestans) (Olofson 1968). Integral model was used for wheat stem rust (Puccinia graminis) crop loss assessment for the first time (Teng 1987).…”
Section: Resultsmentioning
confidence: 99%
“…A case in point is the southern corn leaf blight epiphytotic of 1970, caused by Bipolaris maydis (Y. Nisik. & C. Miyake) Shoemaker, 1959, which affected maize hybrids containing the Texas type (T) cytoplasm in the US Cornbelt, leading to the loss of billions of dollars (Gregory et al, 1978).…”
mentioning
confidence: 99%
“…maydis can cause a very significant loss in yield of corn with cms-T (2,13). Gregory et al (1978) reported that disease severity at the dough stage was critical in yield loss prediction (13). They derived the best regression equation between yield loss and disease severity from the disease assessment made at this stage of the crop.…”
mentioning
confidence: 99%